Let's go through Suzie's steps to determine if she solved the equation correctly.
Starting with the original equation: \[ 9x - 5 = \frac{1}{4}(16x + 60) \]
-
Distribute \(\frac{1}{4}\): \[ 9x - 5 = \frac{1}{4}(16x) + \frac{1}{4}(60) \] Calculating those: \[ 9x - 5 = 4x + 15 \] (Suzie's Step 1 was incorrect; she should have gotten \(9x - 5 = 4x + 15\), not \(9x - 5 = 4x + 60\))
-
Rearranging to isolate variable: From \(9x - 5 = 4x + 15\), we can subtract \(4x\) from both sides: \[ 9x - 4x - 5 = 15 \] This simplifies to: \[ 5x - 5 = 15 \]
-
Adding 5 to both sides: \[ 5x = 20 \]
-
Dividing by 5: \[ x = 4 \]
Since Suzie made a mistake in Step 1, she did not distribute the \(\frac{1}{4}\) correctly to the constant \(60\); therefore, all subsequent steps are based on this mistake.
The correct answer is: Suzie made a mistake on Step 1 - she should have distributed the 1/4 to 60 as well.